The financial crisis and the future of the US dollar as the global reserve currency (Emirates lecture series, 2010)
The dollar's role in the global reserve pool clearly has major implications for its long-term value. Reserve accumulation by countries in the Middle East depends to a large extent on the price of oil. The other region that is likely to play a crucial role is Asia. China and other Asian emerging markets have played a dominant role in the expansion of the global reserve pool over the last decade